2005
DOI: 10.1111/j.1365-2966.2005.09347.x
|View full text |Cite
|
Sign up to set email alerts
|

Millimetre continuum observations of southern massive star formation regions -- I. SIMBA observations of cold cores

Abstract: We report the results of a 1.2-mm continuum emission survey toward 131 star-forming complexes suspected of undergoing massive star formation. These regions have previously been identified as harbouring a methanol maser and/or a radio continuum source [ultracompact (UC) H II region], the presence of which is in most instances indicative of massive star formation. The 1.2-mm emission was mapped using the SIMBA instrument on the 15-m Swedish ESO Submillimetre Telescope (SEST). Emission is detected toward all of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
297
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(314 citation statements)
references
References 30 publications
17
297
0
Order By: Relevance
“…The Cygnus X histograms are also compared to density spectra of nearby dense cores (Motte et al 1998;Ward-Thompson et al 1999) and ρ Oph condensations (Motte et al 1998). dish studies of high-mass star-forming regions (see Table 4 and also Reid & Wilson 2005;Hill et al 2005). Using the terminology mentioned above, HMPOs (for high-mass protostellar objects, Beuther et al 2002) and IRDCs (for infrared dark clouds, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cygnus X histograms are also compared to density spectra of nearby dense cores (Motte et al 1998;Ward-Thompson et al 1999) and ρ Oph condensations (Motte et al 1998). dish studies of high-mass star-forming regions (see Table 4 and also Reid & Wilson 2005;Hill et al 2005). Using the terminology mentioned above, HMPOs (for high-mass protostellar objects, Beuther et al 2002) and IRDCs (for infrared dark clouds, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Serendipitous discoveries of a few infrared-quiet massive young stellar objects have been made in submillimeter continuum maps (e.g. Molinari et al 1998;Motte et al 2003;Sandell & Sievers 2004;Hill et al 2005) and as absorption regions in mid-infrared images (often called "infrared dark clouds", e.g. Carey et al 2000;Rathborne et al 2006).…”
mentioning
confidence: 99%
“…In a study of 16 ALESS SMGs at 0 16 resolution (∼1 kpc), Hodge et al (2016) identified disk-like morphologies with no significant evidence for clumps in dust emission in the majority of their galaxies. However, giant H II regions in local galaxies are a few hundred parsecs across (e.g., Hill et al 2005;Sakamoto et al 2008). This means that, although this study measures structures on ∼1 kpc scales, even higher resolution is required to search for extended clumpy disks with 200-500 pc size clumps, as seen in some simulations (Dekel et al 2009;Bournaud et al 2014) and locally (e.g., Hill et al 2005;Sakamoto et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This fit is done independently for each line of sight, taking into account differences in temperature across the clump better than previous studies (e.g. Faúndez et al 2004;Hill et al 2005), in which a single temperature is assumed for the entire clump. However, for clumps with active star formation, it is possible that the column density is underestimated due temperature gradients along the line of sight.…”
Section: Dust Temperaturesmentioning
confidence: 99%